Developmental trends of delinquent attitudes and behaviors: replications and synthesis across domains, time, and samples - Zhang, Quanwu (Journal of quantitative criminology, 1997)
Inconsistent findings of attitude-behavior relations are commonly attributed to uncontrolled domain, time, or situational factors. Without integrative work, studies accounting for these factors may further complicate research by introducing potentially numerous “third variables” and render a coherent understanding of the attitude-behavior relationship even more difficult to achieve. In this paper, a developmental perspective is taken and the attitude-behavior relationship in delinquency is examined using three modes of investigation: multivariate patterns of attitude-behavior associations, their mutual predictability, and their developmental trajectories. Three grade cohorts of public school boys ( n =1517 of the first, seventh, and tenth grades, initially) were followed over a period of 4 years, with an average age span of 7–16 years. Correspondence analyses suggested that adolescent boys with a tolerant attitude toward theft or violence were more deviant than those who had actual behavior of theft or violence. Stronger attitude effect on subsequent behavior, relative to behavior effect on subsequent attitudes, was found among boys aged 10–12 years. While mean scores of tolerant attitudes to serious theft and violence increased linearly with their behavior counterparts between 6 and 17 years of age, ages 11 and 14 were two turning points at which most delinquent attitudes and behaviors escalated at a higher speed. In general, delinquent attitudes and behaviors were related to each other in various patterns, and age was a defining factor that provided much of the explanation for the inconsistencies in research findings.